2019
DOI: 10.1146/annurev-med-120417-091431
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Susceptibility to Autism Spectrum Disorder

Abstract: The prevalence of autism spectrum disorder (ASD) has been increasing steadily over the last 20 years; however, the molecular basis for the majority of ASD cases remains unknown. Recent advances in next-generation sequencing and detection of DNA modifications have made methylation-dependent regulation of transcription an attractive hypothesis for being a causative factor in ASD etiology. Evidence for abnormal DNA methylation in ASD can be seen on multiple levels, from genetic mutations in epigenetic machinery t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 101 publications
1
69
0
Order By: Relevance
“…DNA methylation has long been implicated as a contributor to the etiology of ASD-related disorders, such as Rett syndrome and Fragile X [ 53 , 54 , 55 , 56 ]. With respect to idiopathic ASD, we were the first to demonstrate that DNA methylation differences across multiple genes could be correlated to dysregulated expression of those genes in LCLs from discordantly diagnosed monozygotic twins and sibling pairs [ 7 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation has long been implicated as a contributor to the etiology of ASD-related disorders, such as Rett syndrome and Fragile X [ 53 , 54 , 55 , 56 ]. With respect to idiopathic ASD, we were the first to demonstrate that DNA methylation differences across multiple genes could be correlated to dysregulated expression of those genes in LCLs from discordantly diagnosed monozygotic twins and sibling pairs [ 7 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is the most commonly studied epigenetic mark and occurs when a methyl group is added to the fifth carbon of cytosine in a cytosine-guanine dinucleotide (CpG) context in mammals. Differential methylation is highly relevant for neuropsychiatric diseases and has been identified in association with schizophrenia [ 37 42 ], depression [ 43 – 46 ], anxiety [ 47 – 50 ], and autism spectrum disorder [ 51 55 ]. Several studies have identified differential methylation patterns in the sperm of humans and rats directly exposed to THC, particularly at the autism candidate locus DLGAP2 , and a study by Watson et al demonstrated that parental THC shifts DNA methylation of genes relevant for glutamatergic signaling in the rat nucleus accumbens [ 56 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, epigenetic processes have emerged as a plausible mechanism by which environmental exposures can lead to long-lasting alterations, such as variation in brain structure or neuronal circuits, found in psychiatric disorders [5][6][7] . There is growing evidence that epigenetic dysregulation is a feature of ADHD 6,[8][9][10][11] , depression 12 , autism [13][14][15][16] , schizophrenia 17,18 and bipolar disorder 19 .…”
Section: Introductionmentioning
confidence: 99%